Pengaruh mintakat ekologi utama terhadap program insentif peningkatan pendapatan kelompok akseptor k.b. di kabupaten Gunung Kidul=The Influence of the Main Ecological Zone on the Progress of Incentive Program for Income - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT The purpose of this investigation is to know how much the difference of influence between physical and social environments of an ecological zone on the Cooperative Effort (UB, Usaha Bersanu2) progress of a family-planning acceptor group given an initial capital incentive for developing the depositing-borrowing activity or other productive and economic acitivities. The investigational method applied is the causal and correlational one by selecting the investigational location of Gunung Kidul regency which can be divided into 3 main ecological zones based on the difference of its physical components, e north zone, central zone, and south zone, as a study material. The data collection is done by interviewing 144 "UB" groups as respondents, taken by means of the stratified purposive sampling representing each zone in balance